A Comparative Analysis On User Satisfaction In Closed And Open Office Buildings: Case Study Of Some Selected Buildings In Abuja - Obasanjo Owoyale Adeola; Barka Jonathan Kwaya; Mohammed Tauheed Alfa (Journal of Contemporary Urban Affairs, 2018)
Many organizations and industries around the world have their own preference for office type base on the nature of services to be rendered. Office building without employee’s satisfaction can adversely affect their performances at their places of work. Open office is an office that has large open space with no partitionable walls but providing workstation for each employee within the open space while the close office is the type with solid walls or frames as partitions with doors which open to each office. It is in light of this that the design of office becomes imperative to both employers and architects. The aim of this study is to investigate user satisfaction and preferences in office buildings, in other to proffer appropriate design suggestion and recommendation that can be used when providing office to employees. A survey is adopted through the aid of administered questionnaire to respondents, and the results are therefore analysed using the simple statistical tool. Findings from the study reveal users satisfaction and preference for open office layout, it further reveals efficiency in users productivity due to its effectiveness in communication, knowledge sharing, space-saving, cost-saving and flexibility in managerial activities. The study, therefore, creates a correlation between findings conducted by other researchers over the years concerning the provision of office for employees their preference and satisfaction for open office buildings.